2017
DOI: 10.1039/c7cc07064k
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis in CuxO/SrTiO3 hybrid allows highly active and stable visible light photocatalytic performance

Abstract: Reversible conversion of Cu and Cu under illumination and with oxidation is demonstrated over CuO/SrTiO. Such Cu/Cu homeostasis together with its photosensitizer function and p-n heterojunction formation has lead to highly active and stable visible photocatalytic performance. This strategy will provide some new insights into the design of highly efficient photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…It also accelerates the creation of e − , and extends the lifetime of e − /h + lifetime, which was ascribed to the potential well made by the Cu 2+ hetero-junction to trap electrons 43 . The separation of electrons and holes results from the electron transfer from TiO 2 to CuO nanoparticles at the interface of CuO (p-type) and the electron-rich of TiO 2 (n-type), which is one possible clarification for the suppressed charge recombination 44 , 45 .…”
Section: Resultsmentioning
confidence: 99%
“…It also accelerates the creation of e − , and extends the lifetime of e − /h + lifetime, which was ascribed to the potential well made by the Cu 2+ hetero-junction to trap electrons 43 . The separation of electrons and holes results from the electron transfer from TiO 2 to CuO nanoparticles at the interface of CuO (p-type) and the electron-rich of TiO 2 (n-type), which is one possible clarification for the suppressed charge recombination 44 , 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure C shows the transient photocurrent responses of AgCl QDs and rGO/AgCl QDs. It was found that rGO/AgCl QDs had showed larger photocurrent density than that of pure AgCl QDs, signifying that charge separation was accelerated effectively in rGO/AgCl QDs . Besides, EIS Nyquist plots of the samples (Figure D) were performed to further evaluate the charge transfer efficiecy.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that rGO/AgCl QDs had showed larger photocurrent density than that of pure AgCl QDs, signifying that charge separation was accelerated effectively in rGO/AgCl QDs. 39,40 Besides, EIS Nyquist plots of the samples ( Figure 6D) were performed to further evaluate the charge transfer efficiecy. It was found that rGO/AgCl QDs exemplified smaller semicircle size than that of bare AgCl QDs, indicating a superior charge separation of photoexcited charges.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of cocatalysts have been used in SrTiO 3 -based photocatalytic systems, such as Pt [10,24] , Co 3 O 4 [10] , NiO x [9,25,26] , MnO x [27] , Cu x O [28,29] , SrCO 3 [14,30] . Among them, NiO x loaded SrTiO 3 is one of the best investigated photocatalytic systems for overall water splitting under UV light.…”
Section: Introductionmentioning
confidence: 99%